Acute effects of vortioxetine and duloxetine on resting-state functional connectivity in the awake rat. (January 2018) - Pérez, Pablo D.; Ma, Zhiwei; Hamilton, Christina; Sánchez, Connie; Mørk, Arne; Pehrson, Alan L.; Bundgaard, Christoffer; Zhang, Nanyin
Abstract: The antidepressant vortioxetine exerts its effects via modulation of several serotonin (5-HT) receptors and inhibition of the 5-HT transporter (SERT). Additionally, vortioxetine has beneficial effects on aspects of cognitive dysfunction in depressed patients. However, a global examination of the drug effect on brain network connectivity is still missing. Here we compared the effects of vortioxetine and a serotonin norepinephrine reuptake inhibitor, duloxetine, on resting-state functional connectivity (RSFC) across the whole brain in awake rats using a combination of pharmacological and awake animal resting-state functional magnetic resonance imaging (rsfMRI) techniques. Our data showed that vortioxetine and duloxetine affected different inter-areal connections with limited overlap, indicating that in addition to different primary target profiles, these two antidepressants have distinct mechanisms of action at the systems level. Further, our data suggest that vortioxetine can affect specific brain areas with distinct 5-HT receptor expression profiles. Taken together, this study demonstrates that the awake animal fMRI approach provides a powerful tool to elucidate the effects of drugs on the brain with high spatial specificity and a global field of view. This capability is valuable to understand how different drugs affect the systems-level brain function, and provides important guidance to dissect specific brain regions and connections for further detailed mechanistic studies. This study also highlights the translational opportunity of the awake animal fMRI approach between preclinical results and human studies. Highlights: We compared the effect of vortioxetine and duloxetine in awake rats using rsfMRI. Vortioxetine and duloxetine affected different connections with limited overlap. Vortioxetine can affect specific brain areas with distinct 5-HT receptor profiles. The study highlights the translational value of the awake animal fMRI approach.